The Effect of Job Satisfaction and Compensation on Employee Performance with Work Motivation as Mediation in 4-Star Hotels Batam City - Diamend Tino Sembiring; Agustinus Setyawan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the impact of job satisfaction and compensation on employee performance in a 4-star hotel in Batam City, utilizing work motivation as a mediator. Job satisfaction and compensation are recognized as crucial factors influencing both work motivation and employee performance. The administration of a questionnaire to 380 hotel employees in Batam City yielded positive and significant correlations between job satisfaction, compensation, work motivation, and employee performance, as revealed by PLS analysis. Work motivation emerges as a significant mediator in the relationships between job satisfaction and employee performance, as well as between compensation and employee performance. Keywords: Employee Performance, Work Motivation, Job Satisfaction, Compensation